CHASING THE STARS- CHALLENGES OF TALENT ACQUISITION IN SMES : Evidence from the IT sector - Kontinen, Hanna (My University, 2019)
This study examines the challenges of talent acquisition in small and medium-sized enterprises operating in the IT sector. The famous war for talent was officially launched in 1998 when McKinsey & Company’s report announced that better talent is worth fighting for. This well- known manifesto was made almost 20 years ago, but the title is still a reality and describes perfectly the situation in today’s talent market and the talent acquisition challenges companies are facing. The war is still being fought as more and more companies are focusing on the challenges of attracting and managing the star employees who create the biggest competitive advantage to firms. Also, it seems that the challenge is even bigger in the IT sector, where the scarcity of talent is on a critical level. It seems that despite of being a differentiator between organizations that succeed and those that do not, talent acquisition includes a lot of uncertainties, unclarity, and misunderstandings. The aim of this study is to provide more insights to this phenomenon by exploring academic literature and combining it with the empirical research. The empirical data of the research is collected through semi-structured theme interviews with the representatives of six small and medium- sized enterprises operating in the IT field in Finland. The data is analyzed by utilizing content analysis. The main findings of the study indicate that there are several factors affecting the challenges companies face while operating on the talent market. Based on the research data these challenges can be divided into four different themes; awareness, employer brand, organizational structure and changes in the labor market. All these factors were affecting the talent management processes of the representative companies. In spite of the exponential growth of this field of research during the last few decades, there are still some unanswered questions and findings that need to be addressed. The contribution of this study is to illustrate the current state of talent acquisition and highlight the actual challenges on this field, focusing especially on companies operating on the IT field. In terms of contributions to practice, companies should pay more attention to the real reasons behind the talent acquisition challenge. Only by understanding the actual problem companies can target their talent acquisition actions on right direction and problem. Also, identifying and understanding the processes in a wider context might provide a greater understanding for both practitioners and business leaders.
Keywords: Talent acquisition, Recruitment, Talent Management, Employer branding, Information technology; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Henkilöstöjohtamisen maisteriohjelma|en=Master's Programme in Human Resource Management|